Classification and scoring systems used in diagnostics, prognosis and the treatment of proximal digestive tract bleeding - Benedeto-Stojanov Daniela; Nagorni Aleksandar; Bjelaković Goran; Petrović Gordana; Stojanov Dragan; Đenić Nebojša (Vojnosanitetski Pregled)
nema